Environmental movements, democracy and identity in Bolivia and Peru: two divergent andean experiences | Movimentos ambientalistas, democracia e identidade na Bolívia e no Peru: duas experiências andinas divergentes - Almeida, Leonardo; Carvalho, Lucas Martins (Mural Internacional, 2021)
This research investigates the conditions behind the emergence of organized environmental movements in Bolivia and their less prominence in Peru. It seeks to understand why environmental movements in Bolivia, unlike in Peru, emerge with political opportunities, organizational strength through broad-based coalitions and collective consciousness. The analysis relied on case studies in Bolivia and Peru to assess the political process model theory while providing some alterations to its original theoretical framework by demonstrating the role of transnational networks in supporting environmental movements’ legitimacy. Through a literature review and a qualitative approach, the research examined the internal workings of the political process model theory through a comparative historical analysis on environmental movements under neoliberal times starting from the 1980s onwards and its implications to democracy. Keywords: Bolivia; environmental movements; Peru. RESUMO Essa pesquisa analisa as condições referentes à emergência de movimentos ambientalistas na Bolívia e seu menor protagonismo no Peru. O artigo busca compreender as razões para a emergência de movimentos ambientalistas na Bolívia levando em conta o contexto político, a capacidade organizacional através de redes de coalizão e a conscientização de uma identidade coletiva. Para tal, a análise focou-se nos estudos de caso da Bolívia e do Peru com o intuito de demonstrar os impactos de redes transnacionais na dinâmica de legitimação de movimentos ambientalistas. Através da revisão bibliográfica e da abordagem qualitativa, a pesquisa utilizou instrumentos da teoria do processo político para analisar comparativamente o histórico de movimentos ambientalistas no contexto do neoliberalismo a partir da década de 1980 e suas implicações para a democracia. Palavras-chave: Bolívia; movimentos ambientais; Peru. Recebido em: 31 mai. 2021 | Aceito em: 09 nov. 2021.